Optimizing sustainability reporting through business process automation and innovation: Insights from technology acceptance and diffusion theories - Ramadhan, Syahril; Nugroho, Arissetyanto; Darmansyah, Darmansyah (Proceeding International Conference on Accounting and Finance, 2024)
The study's key findings emphasize the pivotal role of perceived advantages and ease of use in shaping attitudes towards Business Process Automation (BPA) within sustainable development reporting. While a perceived relative advantage in BPA usage is linked to recognizing its utility, it doesn't necessarily extend to an ease-of-use perspective. The research underscores the importance of trialability, indicating that hands-on experience positively influences views on BPA's usefulness and ease of use. Interestingly, factors like compatibility with existing practices and complexity have limited impact on perceptions. The study also reveals that observability, including the visibility of benefits and social influence, might not be primary drivers for BPA adoption in sustainable development reporting. In conclusion, the research contributes valuable insights for strategically implementing BPA, integrating factors like trialability and perceived advantages, informed by the Innovation Diffusion Theory and the Technology Acceptance Model. This comprehensive framework aims to enhance data accuracy, efficiency, and decision-making processes, aligning with broader sustainability and environmental performance goals.